The king's speech (Burbank : Starz, 2004)
After the death of his father King George V (Michael Gambon of HARRY POTTER AND THE HALF-BLOOD PRINCE) and the scandalous abdication of King Edward VIII (Guy Pearce of MEMENTO), Bertie (Academy-Award®-winner Colin Firth) who has suffered from a debilitating speech impediment all his life, is suddenly crowned King George VI of England. With his country on the brink of war and in desperate need of a leader, his wife, Elizabeth (Golden-Globe®-nominee Helena Bonham Carter), the future Queen Mother, arranges for her husband to see an eccentric speech therapist, Lionel Logue (Academy-Award®-winner Geoffrey Rush). After a rough start, the two delve into an unorthodox course of treatment and eventually form an unbreakable bond. With the support of Logue, his family, his government and Winston Churchill (Timothy Spall of SWEENEY TODD), the King will overcome his stammer and deliver a radio-address that inspires his people and unites them in battle
Keywords: Drama